Pengembangan Media Pembelajaran Berbasis Android Untuk Mata Pelajaran Simulasi Digital Materi Pokok Perangkat Lunak Pengolah Aangka di Kelas X UPW 1 SMK Negeri 3 Samarinda Tahun Ajaran 2017/2018 - Hetin Tandi Arru; Arif Harjanto (Institut Informatika dan Bisnis Darmajaya, 2018)
This study is based on the lack of use of android-based learning media that impact on the way some schools view in responding to smartphone usage by students, the school considered that the use of smartphones in the school environment can negatively impact the learning process so prohibit the use of smartphones by students in the school environment. The results showed that: (1) Android-based learning media for digital simulation subjects principal subject of this numerical processing software successfully developed (2) Application of this Android-based learning media received good response from students (3) 4.65 average with the category of